sed -r 's/^(.).*$/\1/g'
g="global" flag for replace
what to match:
^ = beginning of line
(.) = a character. sourround it in parenthesis to refer to it later as backreference #1 (the \1)
.* = any characters following
$ = end of line
what to replace it with:
\1 = the captured expression in the previous section of the s command
the -r switch i've put it mostly so I don't have to escape the parenthesis, otherwise it would have look like this:
sorry i just see you only need to do this operation in lines beginning with a "+", this will do:
sed -r '/\+/s/^(.).*$/\1/g'
Of course, since you already know you'll use always a "+" for replacement you could leave it fixed too:
sed -r 's/^\+.*$/+/g'